The Effect Of The Sharia Supervisory Board (SSB) And Financial Performance On The Disclosure Of The Islamic Social Report (ISR) Analysis Before And After The Merger: (Case Studies on Companies of Bank BRI Syariah, Bank Syariah Mandiri, and Bank BNI Syariah Listed on the Indonesia Stock Exchange for the 2020-2021 Period) - Winda Auliza; Murniati Murniati (Indonesia Banking School, 2023)
This study aims to examine the influence of the sharia supervisory board and financial performance on Islamic Social Reporting before and after the merger to become Bank Syariah Indonesia. Financial performance is proxied using ROA, the population in this study are Islamic banks listed on the Indonesia Stock Exchange operating in 2020-2021. The sampling technique used a purposive sampling technique, and 4 samples were obtained. The analytical method used to test the hypothesis is the Different Test and multiple regression analysis. The results of this study indicate that the sharia supervisory board has effect on Islamic Social Reporting (ISR), while financial performance has effect on Islamic Social Reporting (ISR). The sharia supervisory board and financial performance have an influence on Islamic Social Reporting (ISR).